Copper / steel composite material with high bonding strength and preparation method

By using a specific composition of intermediate flux-core welding wire and surfacing cladding technology, the penetration cracks and residual stress problems of copper/steel composites at the interface are solved, and high bond strength and good mechanical properties are achieved, which are suitable for a variety of copper/steel structural parts.

CN116275691BActive Publication Date: 2025-08-15XIAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310104300.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-13
Publication Date
2025-08-15
Estimated Expiration
2043-02-13

AI Technical Summary

Technical Problem

Existing copper/steel composite materials are prone to permeability cracks and residual stresses at the interface, resulting in the problems of low preparation accuracy and low material utilization, especially in the preparation of ultra-thick plates.

Method used

A specific composition of the intermediate layer flux-core welding wire, including cobalt powder, iron powder, manganese powder, molybdenum powder, silicon powder and carbon powder, is used to form a copper/steel composite material with high bond strength through the surfacing and cladding technology of the silicon bronze wire layer and the low carbon steel layer.

Benefits of technology

It effectively reduces liquefied cracks and residual stresses at the copper/steel interface, improves the bonding strength and mechanical properties of the material, and is suitable for a variety of copper/steel structural parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116275691B_ABST
    Figure CN116275691B_ABST
Patent Text Reader

Abstract

The present invention discloses a copper / steel composite material with high bonding strength. The composite material comprises a silicon bronze welding wire layer, an intermediate layer, and a low-carbon steel layer, arranged in sequence. The silicon bronze welding wire layer is produced by surfacing with silicon bronze welding wire, the intermediate layer is produced by cladding with an intermediate layer flux-cored welding wire, and the low-carbon steel layer is a low-carbon steel plate. The intermediate layer flux-cored welding wire used in the composite material effectively reduces liquefaction cracks and residual stress at the copper / steel interface. The resulting high-bond-strength copper / steel composite material exhibits excellent mechanical properties. A method for preparing the high-bond-strength copper / steel composite material is also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of metal materials, and in particular relates to a copper / steel composite material with high bonding strength, and also relates to a preparation method of the copper / steel composite material with high bonding strength. Background Art

[0002] Copper, with its excellent ductility and superior electrical and thermal conductivity, is a commonly used industrial metal material, widely used in numerous fields. However, copper's low strength, tendency to deform during use, and high price have hindered the long-term development of copper and its alloys. Steel's low price and high strength can offset copper's disadvantages in mechanical properties and cost. When combined with copper, steel can fully utilize the properties of copper while fully exploiting the mechanical properties of steel. Copper / steel composites offer excellent overall mechanical properties and strong economic benefits. Consequently, copper / steel composite structural components are widely used in military and power electronics fields.

[0003] Currently, copper / steel composites are primarily fabricated using explosive welding. This method is dangerous, has low fabrication precision, and results in low material utilization. More importantly, during the fabrication of ultra-thick plates, cracking often occurs at the interface, leading to failure of the copper / steel composite. Fusion welding, on the other hand, is not immune to permeation cracking at the copper-steel interface. To address the complex fabrication process for copper / steel composites, a copper-based flux-cored wire was designed and developed to address the permeation cracking and excessive residual stress that can occur at the copper / steel interface during welding. Summary of the Invention

[0004] The first object of the present invention is to provide a copper / steel composite material with high bonding strength. By selecting a specific flux-cored welding wire as an intermediate layer, the resulting composite material has good mechanical properties and can meet the use requirements of preparing such a high bonding strength copper / steel composite material.

[0005] A second object of the present invention is to provide a method for preparing a copper / steel composite material having high bonding strength.

[0006] The first technical solution adopted by the present invention is that the copper / steel composite material with high bonding strength comprises a silicon bronze welding wire layer, an intermediate layer and a low carbon steel layer arranged in sequence;

[0007] The silicon bronze wire layer is made by surfacing silicon bronze wire, the middle layer is made by cladding middle layer flux-cored wire, and the low carbon steel layer is a low carbon steel plate.

[0008] The present invention is also characterized in that

[0009] The intermediate layer flux-cored welding wire includes a flux core and a welding sheath, wherein the flux core is composed of the following components by mass percentage: 25% to 30% cobalt powder; 4% iron powder; 2% manganese powder; 5% to 10% molybdenum powder; 1.5% silicon powder; 1.5% carbon powder; and copper powder as the remainder. The sum of the mass percentages of the above components is 100%. The outer sheath of the flux-cored welding wire is a copper strip with a filling rate of 30wt.% to 32wt.%.

[0010] The second technical solution adopted by the present invention is a method for preparing a copper / steel composite material with high bonding strength, and the specific operating steps are as follows:

[0011] Step 1: Preparation of intermediate layer flux-cored wire:

[0012] Weigh the raw material powders according to mass percentage: cobalt powder 25% to 30%; iron powder 4%; manganese powder 2%; molybdenum powder: 5% to 10%; silicon powder 1.5%; carbon powder 1.5%; copper powder as the balance; the sum of the mass percentages of the above components is 100%;

[0013] Step 2: The raw material powder weighed above is used as the flux core, and the copper strip is used as the welding wire sheath, with a filling rate of 30wt.%-32wt.%, and the required welding wire is made by a wire drawing machine, and the prepared welding wire is dried in a muffle furnace;

[0014] Step 3: Select a low-carbon steel plate as the workpiece substrate, use an angle grinder to grind the surface oxide scale, use ultrasonic cleaning equipment to remove impurities after grinding, and then place the low-carbon steel plate in a drying furnace for storage;

[0015] Step 4: Preheat the low-carbon steel plate prepared in step 3, and then use an AC TIG welder to clad the flux-cored wire prepared in step 2 on the low-carbon steel plate to complete the preparation of the low-carbon steel layer-intermediate layer, with the stacking height of the intermediate layer being 5 mm to 10 mm;

[0016] Step 5: Grind the oxide scale on the plate obtained in step 4, and use silicon bronze welding wire to build up a silicon bronze welding wire layer on the surface of the middle layer, with a stacking height of 20 mm to 40 mm;

[0017] Step 6: After the sample in step 5 has cooled to room temperature, use mechanical cleaning to polish away impurities on the surface and remove post-weld slag to facilitate test sampling.

[0018] The present invention is also characterized in that

[0019] The drying temperature in step 2 is 180° C. to 200° C., and the drying time is 1 to 2 hours.

[0020] In step 4, preheating is performed using a TIG welding machine without wire filling, the preheating current is 130A-140A, and the preheating time is 10s.

[0021] The process parameters used in step 4 are: welding current of 150-170A, cladding voltage of 22-25V, tungsten electrode extension length of 3mm, swing arc width of 6mm, welding speed of 400mm / min, and argon gas flow rate of 10-12L / min.

[0022] In step 4, the welding current of the deposited silicon bronze wire is 150A-160A, the voltage is 25V-27V, the tungsten electrode extension length is 3mm, the swing arc width is 4mm, the welding speed is 500mm / min, and the argon gas flow rate is 10L / min-12L / min.

[0023] The beneficial effects of the present invention are:

[0024] (1) The flux-cored welding wire designed in the present invention can effectively reduce the liquefaction cracks and residual stress at the copper / steel interface, and the prepared high-bonding-strength copper / steel composite material has good mechanical properties.

[0025] (2) The flux-cored welding wire of the present invention can also be applied to other copper / steel structural parts, not limited to Q235 steel and silicon bronze, and provides a new filling material for the connection of copper / steel heterogeneous materials.

[0026] (3) The preparation method of the copper / steel composite material with high bonding strength of the present invention is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a microstructure diagram of the copper / steel composite material with high bonding strength prepared in Example 1 of the present invention;

[0028] Figure 2 This is a macroscopic image of the copper / steel composite material with high bonding strength prepared in Example 1 of the present invention;

[0029] Figure 3 It is a schematic structural diagram of the copper / steel composite material with high bonding strength prepared by the present invention.

[0030] In the figure, 1. Silicon bronze welding wire layer, 2. Middle layer, 3. Low carbon steel layer. DETAILED DESCRIPTION

[0031] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments.

[0032] The present invention provides a copper / steel composite material with high bonding strength, such as Figure 3 As shown, it includes a silicon bronze welding wire layer 1, an intermediate layer 2 and a low carbon steel layer 3 arranged in sequence;

[0033] The silicon bronze welding wire layer 1 is made by surfacing silicon bronze welding wires, the middle layer 2 is made by cladding middle layer flux-cored welding wires, and the low carbon steel layer 3 is a low carbon steel plate.

[0034] The intermediate layer flux-cored welding wire includes a flux core and a welding sheath, wherein the flux core is composed of the following components by mass percentage: 25% to 30% cobalt powder; 4% iron powder; 2% manganese powder; 5% to 10% molybdenum powder; 1.5% silicon powder; 1.5% carbon powder; and copper powder as the remainder. The sum of the mass percentages of the above components is 100%. The outer sheath of the flux-cored welding wire is a copper strip with a filling rate of 30wt.% to 32wt.%.

[0035] The present invention also provides a method for preparing a copper / steel composite material with high bonding strength, the specific steps of which are:

[0036] Step 1: Preparation of intermediate layer flux-cored wire:

[0037] Weigh the raw material powders according to mass percentage: cobalt powder 25% to 30%; iron powder 4%; manganese powder 2%; molybdenum powder: 5% to 10%; silicon powder 1.5%; carbon powder 1.5%; copper powder as the balance; the sum of the mass percentages of the above components is 100%;

[0038] The powders are all 200-300 mesh. After being weighed, the powders are dried in a vacuum tube furnace at a temperature of 120°C for 2 hours.

[0039] Step 2: The raw material powder weighed above is used as the flux core, and the copper strip is used as the welding wire sheath, with a filling rate of 30wt.%-32wt.%, and the required welding wire is made by a wire drawing machine, and the prepared welding wire is dried in a muffle furnace; the drying temperature in step 2 is 180℃~200℃, and the drying time is 1~2h.

[0040] Step 3: Select a low-carbon steel plate (Q235 plate) of appropriate size as the workpiece substrate, use an angle grinder to grind the surface oxide scale, use ultrasonic cleaning equipment to remove impurities after grinding, and then place the low-carbon steel plate in a drying furnace for storage;

[0041] Step 4: Preheat the mild steel plate prepared in step 3, and then use an AC TIG welder to clad the flux-cored wire prepared in step 2 on the mild steel plate to prepare the mild steel layer 3-intermediate layer 2, with the stacking height of the intermediate layer 2 being 5 mm to 10 mm;

[0042] In step 4, preheating is performed using a TIG welding machine without wire filling, the preheating current is 130A-140A, and the preheating time is 10s.

[0043] The process parameters used in step 4 are: welding current of 150-170A, cladding voltage of 22-25V, tungsten electrode extension length of 3mm, swing arc width of 6mm, welding speed of 400mm / min, and argon gas flow rate of 10-12L / min.

[0044] In step 4, the welding current of the deposited silicon bronze wire is 150A-160A, the voltage is 25V-27V, the tungsten electrode extension length is 3mm, the swing arc width is 4mm, the welding speed is 500mm / min, and the argon gas flow rate is 10L / min-12L / min.

[0045] Step 5: Grind the oxide scale on the plate obtained in step 4, and use silicon bronze welding wire to build up the surface of the middle layer to form a silicon bronze welding wire layer 1 with a build-up height of 20 mm to 40 mm;

[0046] Step 6: After the sample in step 5 has cooled to room temperature, use mechanical cleaning to polish away impurities on the surface and remove post-weld slag to facilitate test sampling.

[0047] Example 1

[0048] Step 1: Preparation of intermediate layer flux-cored welding wire: Weigh the raw material powders by mass percentage: cobalt powder 25%; iron powder 4%; manganese powder 2%; molybdenum powder: 5%; silicon powder 1.5%; carbon powder 1.5%; copper powder 61%, and the sum of the mass percentages of the above components is 100%;

[0049] Step 2: The raw material powder weighed above is used as the flux core, and the copper strip is used as the welding wire sheath, with a filling rate of 30wt.%, and the required welding wire is made by a wire drawing machine. The prepared welding wire is dried in a muffle furnace at a drying temperature of 180°C and a drying time of 1 hour;

[0050] Step 3: Select a Q235 plate with a size of 80×100×10mm as the workpiece substrate, use an angle grinder to grind the surface oxide scale, use ultrasonic cleaning equipment to remove impurities after grinding, and then place the steel plate in an electronic moisture-proof cabinet for storage;

[0051] Step 4: Preheat the mild steel plate prepared in step 3 by using a TIG welder without wire filling. The preheating current is 130A and the preheating time is 10s. Then, an AC TIG welder is used to clad the flux-cored wire prepared in step 2 on the mild steel plate. The welding current is 150A, the cladding voltage is 22V, the tungsten electrode extension length is 3mm, the swing arc width is 6mm, the welding speed is 400mm / min, and the argon gas flow rate is 10L / min. The preparation of the mild steel layer 3-intermediate layer 2 is completed. The stacking height of the intermediate layer 2 is 5mm.

[0052] Step 5: Grind the oxide scale that appeared in step 4 and use silicon bronze welding wire to build up the surface of the transition layer. The build-up height is 20 mm, the welding current is 150 A, the voltage is 25 V, the tungsten electrode extension length is 3 mm, the swing arc width is 4 mm, the welding speed is 500 mm / min, the argon gas flow rate is 10 L / min, and the diameter of the silicon bronze welding wire is 1.2 mm.

[0053] Step 6: After the sample in step 5 has cooled to room temperature, use mechanical cleaning to polish away impurities on the surface and remove post-weld slag to facilitate test sampling.

[0054] like Figure 1 As shown in FIG, the copper / steel composite material prepared in Example 1, through microstructural observation, no penetration cracks were found at the copper / steel connection interface under a low-power microscope, which will be beneficial to improving the mechanical properties of the copper / steel interface; Figure 2 As shown, the middle layer has good formability, high density, no copper alloy welding defects such as pores, and good bonding between the middle layer and the steel; after tensile test, the yield strength is 218.5MPa, the tensile strength is 325.4MPa, the impact absorption energy is 32kJ, and the average microhardness of the middle layer is 135HV 0.1 .

[0055] Example 2

[0056] Step 1: Preparation of intermediate layer flux-cored welding wire: Weigh the raw material powders by mass percentage: cobalt powder 25%; iron powder 4%; manganese powder 2%; molybdenum powder: 7%; silicon powder 1.5%; carbon powder 1.5%; copper powder 59%, and the sum of the mass percentages of the above components is 100%;

[0057] Step 2: The raw material powder weighed above is used as the flux core, and the copper strip is used as the welding wire sheath, with a filling rate of 32wt.%, and the required welding wire is made by a wire drawing machine. The prepared welding wire is dried in a muffle furnace at a temperature of 190°C for 1.5 hours;

[0058] Step 3: Select a Q235 plate with a size of 80×100×10mm as the workpiece substrate, use an angle grinder to grind the surface oxide scale, use ultrasonic cleaning equipment to remove impurities after grinding, and then place the steel plate in an electronic moisture-proof cabinet for storage;

[0059] Step 4: Preheat the mild steel plate prepared in step 3 by using a TIG welder without wire filling. The preheating current is 135A and the preheating time is 10s. Then, an AC TIG welder is used to clad the flux-cored wire prepared in step 2 on the mild steel plate. The welding current is 160A, the cladding voltage is 23V, the tungsten electrode extension length is 3mm, the swing arc width is 6mm, the welding speed is 400mm / min, and the argon gas flow rate is 12L / min. The preparation of the mild steel layer 3-intermediate layer 2 is completed. The stacking height of the intermediate layer 2 is 10mm.

[0060] Step 5: Grind the oxide scale that appeared in step 4 and use silicon bronze wire to build up the transition layer surface. The build-up height is 30 mm, the welding current is 155 A, the voltage is 26 V, the tungsten electrode extension length is 3 mm, the swing arc width is 4 mm, the welding speed is 500 mm / min, the argon gas flow rate is 12 L / min, and the diameter of the silicon bronze wire is 1.2 mm.

[0061] Step 6: After the sample in step 5 has cooled to room temperature, use mechanical cleaning to polish away impurities on the surface and remove post-weld slag to facilitate test sampling.

[0062] The copper / steel composite material prepared in Example 2 was observed by microstructure observation. No penetration cracks were found at the copper / steel connection interface under a low-power microscope, which will be beneficial to improving the mechanical properties of the copper / steel interface. The tensile test showed that the yield strength was 223.5 MPa, the tensile strength was 321.4 MPa, the impact absorption energy was 30.2 kJ, and the average microhardness of the transition layer was 130 HV. 0.1 .

[0063] Implementation Example 3

[0064] Step 1: Preparation of intermediate layer flux-cored welding wire: Weigh the raw material powders by mass percentage: 30% cobalt powder; 4% iron powder; 2% manganese powder; 10% molybdenum powder; 1.5% silicon powder; 1.5% carbon powder; 51% copper powder, and the sum of the mass percentages of the above components is 100%;

[0065] Step 2: The raw material powder weighed above is used as the flux core, and the copper strip is used as the welding wire sheath with a filling rate of 31wt.%. The required welding wire is made by a wire drawing machine, and the prepared welding wire is dried in a muffle furnace at a temperature of 200°C for 2 hours.

[0066] Step 3: Select a Q235 plate with a size of 80×100×10mm as the workpiece substrate, use an angle grinder to grind the surface oxide scale, use ultrasonic cleaning equipment to remove impurities after grinding, and then place the steel plate in an electronic moisture-proof cabinet for storage;

[0067] Step 4: Preheat the mild steel plate prepared in step 3 using a TIG welder without wire filling, with a preheating current of 140 A and a preheating time of 10 s. Then, use an AC TIG welder to clad the flux-cored wire prepared in step 2 on the mild steel plate with a welding current of 170 A, a cladding voltage of 25 V, a tungsten electrode extension length of 3 mm, an arc width of 6 mm, a welding speed of 400 mm / min, and an argon gas flow rate of 12 L / min. The preparation of the mild steel layer 3-intermediate layer 2 is completed, and the stacking height of the intermediate layer 2 is 6 mm.

[0068] Step 5: Grind the oxide scale that appeared in step 4 and use silicon bronze wire to build up the transition layer surface. The build-up height is 40 mm, the welding current is 160 A, the voltage is 27 V, the tungsten electrode extension length is 3 mm, the swing arc width is 4 mm, the welding speed is 500 mm / min, the argon gas flow rate is 12 L / min, and the diameter of the silicon bronze wire is 1.2 mm.

[0069] Step 6: After the sample in step 5 has cooled to room temperature, use mechanical cleaning to polish away impurities on the surface and remove post-weld slag to facilitate test sampling.

[0070] The copper / steel composite material prepared in Example 3 was observed by microstructure observation. No penetration cracks were found at the copper / steel interface under a low-power microscope, which will be beneficial to improving the mechanical properties of the copper / steel interface. The tensile test showed that the fracture positions were all on the copper side, with a yield strength of 240.1 MPa, a tensile strength of 320.4 MPa, an impact absorption energy of 29.6 kJ, and an average microhardness of the transition layer of 147.6 HV. 0.1 .

[0071] Implementation Example 4

[0072] Step 1: Preparation of intermediate layer flux-cored welding wire: Weigh the raw material powders by mass percentage: cobalt powder 28%; iron powder 2%; manganese powder 2%; molybdenum powder: 7%; silicon powder 1.5%; carbon powder 1.5%; copper powder 56%, and the sum of the mass percentages of the above components is 100%;

[0073] Step 2: The raw material powder weighed above is used as the flux core, and the copper strip is used as the welding wire sheath, with a filling rate of 30wt.%, and the required welding wire is made by a wire drawing machine, and the prepared welding wire is dried in a muffle furnace;

[0074] Step 3: Select a Q235 plate with a size of 80×100×10mm as the workpiece substrate, use an angle grinder to grind the surface oxide scale, use ultrasonic cleaning equipment to remove impurities after grinding, and then place the steel plate in an electronic moisture-proof cabinet for storage;

[0075] Step 4: Preheat the mild steel plate prepared in step 3 using a TIG welder without wire filling, with a preheating current of 130 A, a preheating time of 10 s, and a welding speed of 300 mm / min. The flux-cored wire prepared in step 2 is clad on the mild steel plate using an AC TIG welder with a welding current of 160 A, a cladding voltage of 24 V, a tungsten electrode extension length of 3 mm, an arc width of 6 mm, a welding speed of 400 mm / min, and an argon gas flow rate of 12 L / min. The preparation of the mild steel layer 3-intermediate layer 2 is completed, and the stacking height of the intermediate layer 2 is 7 mm.

[0076] Step 5: Grind the oxide scale that appeared in step 4 and use silicon bronze wire to build up the transition layer surface. The build-up height is 20 mm, the welding current is 155 A, the voltage is 26 V, the tungsten electrode extension length is 3 mm, the swing arc width is 4 mm, the welding speed is 500 mm / min, the argon gas flow rate is 10 L / min, and the diameter of the silicon bronze wire is 1.2 mm.

[0077] Step 6: After the sample in step 5 has cooled to room temperature, use mechanical cleaning to polish away impurities on the surface and remove post-weld slag to facilitate test sampling.

[0078] The copper / steel composite material prepared in Example 4 was observed by microstructure observation. No penetration cracks were found at the copper / steel connection interface under a low-power microscope, which will be beneficial to improving the mechanical properties of the copper / steel interface. The tensile test showed that the yield strength was 231.6 MPa, the tensile strength was 319.8 MPa, the impact absorption energy was 31.1 kJ, and the average microhardness of the intermediate layer was 142.3 HV. 0.1 .

[0079] Example 5

[0080] Step 1: Preparation of intermediate layer flux-cored welding wire: Weigh the raw material powders by mass percentage: cobalt powder 27%; iron powder 4%; manganese powder 2%; molybdenum powder: 5%; silicon powder 1.5%; carbon powder 1.5%; copper powder 59%, and the sum of the mass percentages of the above components is 100%;

[0081] Step 2: The raw material powder weighed above is used as the flux core, and the copper strip is used as the welding wire sheath, with a filling rate of 32wt.%, and the required welding wire is made by a wire drawing machine, and the prepared welding wire is dried in a muffle furnace;

[0082] Step 3: Select a Q235 plate with a size of 80×100×10mm as the workpiece substrate, use an angle grinder to grind the surface oxide scale, use ultrasonic cleaning equipment to remove impurities after grinding, and then place the steel plate in an electronic moisture-proof cabinet for storage;

[0083] Step 4: Preheat the mild steel plate prepared in step 3 by using a TIG welder without wire filling. The preheating current is 130A, the preheating time is 10s, and the welding speed is 300mm / min. The flux-cored wire prepared in step 2 is clad on the mild steel plate using an AC TIG welder. The welding current is 150A, the cladding voltage is 24V, the tungsten electrode extension length is 3mm, the swing arc width is 6mm, the welding speed is 400mm / min, and the argon gas flow rate is 10L / min. The preparation of the mild steel layer 3-intermediate layer 2 is completed, and the stacking height of the intermediate layer 2 is 8mm.

[0084] Step 5: Grind the oxide scale that appeared in step 4 and use silicon bronze wire to build up the transition layer surface. The build-up height is 20 mm, the welding current is 150 A, the voltage is 25 V, the tungsten electrode extension length is 3 mm, the swing arc width is 4 mm, the welding speed is 500 mm / min, the argon gas flow rate is 12 L / min, and the diameter of the silicon bronze wire is 1.2 mm.

[0085] Step 6: After the sample in step 6 has cooled to room temperature, mechanically clean the surface impurities and remove the post-weld slag to facilitate test sampling.

[0086] The copper / steel composite material prepared in Example 5 was observed by microstructure observation. No penetration cracks were found at the copper / steel connection interface under a low-power microscope, which will be beneficial to improving the mechanical properties of the copper / steel interface. The tensile test showed that the yield strength was 238.4 MPa, the tensile strength was 322.7 MPa, the impact absorption energy was 32.8 kJ, and the average microhardness of the intermediate layer was 145.1 HV. 0.1 .

Claims

1. A copper / steel composite material with high bonding strength, characterized in that: It comprises a silicon bronze welding wire layer (1), an intermediate layer (2) and a low carbon steel layer (3) which are arranged in sequence; The silicon bronze welding wire layer (1) is made by surfacing silicon bronze welding wire, the middle layer (2) is made by cladding middle layer flux-cored welding wire, and the low carbon steel layer (3) is a low carbon steel plate; The intermediate layer flux-cored welding wire includes a flux core and a welding sheath, wherein the flux core is composed of the following components by mass percentage: 25% to 30% cobalt powder; 4% iron powder; 2% manganese powder; 5% to 10% molybdenum powder; 1.5% silicon powder; 1.5% carbon powder; and copper powder as the balance. The sum of the mass percentages of the above components is 100%. The outer sheath of the flux-cored welding wire is a copper strip with a filling rate of 30wt.% to 32wt.%.

2. The method for preparing the copper / steel composite material with high bonding strength according to claim 1, characterized in that: The specific steps are: Step 1: Preparation of intermediate layer flux-cored wire: Weigh the raw material powders according to mass percentage: cobalt powder 25%-30%; iron powder 4%; manganese powder 2%; molybdenum powder: 5%-10%; silicon powder 1.5%; carbon powder 1.5%; copper powder as the balance; the sum of the mass percentages of the above components is 100%; Step 2: The raw material powder weighed above is used as the flux core, and the copper strip is used as the welding wire sheath, with a filling rate of 30wt.%-32wt.%, and the required welding wire is made by a wire drawing machine, and the prepared welding wire is dried in a muffle furnace; Step 3: Select a low-carbon steel plate as the workpiece substrate, use an angle grinder to grind the surface oxide scale, use ultrasonic cleaning equipment to remove impurities after grinding, and then place the low-carbon steel plate in a drying furnace for storage; Step 4: preheating the low-carbon steel plate prepared in step 3, and then using an AC TIG welding machine to clad the flux-cored wire prepared in step 2 on the low-carbon steel plate to complete the preparation of the low-carbon steel layer (3)-intermediate layer (2), with the stacking height of the intermediate layer (2) being 5 mm to 10 mm; Step 5: Grind the oxide scale on the plate obtained in step 4, and use silicon bronze welding wire to build up the silicon bronze welding wire layer (1) on the surface of the middle layer, with a stacking height of 20 mm to 40 mm; Step 6: After the sample in step 5 has cooled to room temperature, use mechanical cleaning to polish away impurities on the surface and remove post-weld slag to facilitate test sampling.

3. The method for preparing the copper / steel composite material with high bonding strength according to claim 2, characterized in that: The drying temperature in step 2 is 180°C to 200°C, and the drying time is 1 to 2 hours.

4. The method for preparing the copper / steel composite material with high bonding strength according to claim 2, characterized in that: In step 4, preheating is performed using a TIG welding machine without wire filling, the preheating current is 130A-140A, and the preheating time is 10s.

5. The method for preparing the copper / steel composite material with high bonding strength according to claim 2, characterized in that: The process parameters used in step 4 are: welding current of 150~170A, cladding voltage of 22~25V, tungsten electrode extension length of 3mm, swing arc width of 6mm, welding speed of 400mm / min, and argon gas flow rate of 10~12L / min.

6. The method for preparing the copper / steel composite material with high bonding strength according to claim 2, characterized in that: In step 5, the welding current of the deposited silicon bronze wire is 150A~160A, the voltage is 25V~27V, the tungsten electrode extension length is 3mm, the swing arc width is 4mm, the welding speed is 500mm / min, and the argon gas flow rate is 10L / min~12L / min.

Citation Information

Patent Citations

  • Ni based-flux-cored wire and method for preparing copper-steel base gradient composite

    CN111558793A